HUBUNGAN i iPENGETAHUAN, iPERSEPSI iDAN iPERAN iTENAGA iKESEHATAN i i iDENGAN iSTIGMA iTERHADAP i iORANG i POSITIF iCOVID-19 iPADA iMASYARAKAT iKOTA iKENDARI i TAHUN i2020 - Ferli Faemu; Hariati Lestari; Jumakil Jumakil (Endemis Journal, 2022)
Stigma iis ia ifrom iof iassessment idistortion iof ia icommunity ion ian iindividual iin isocial iinteractions. iThis istigma iarises ifrom ithe ihigh irisk iof idisease iinfection iand ia ilock iof iknowledge ifactors ithat icause ipublic istigma ion ithe iCOVID-19 iare ithe ilevel iof iknowledge ithat ieffects iindividual iperceptions iand iactions iand ithe idissemination iof inon-credible iinformation. iThis istudy iaimed ito idetermine ithe irelationship iof istigma iwith iknowlwdge iand iperceptions ias iwell ias i ithe irole iof ihealth iworkers itowards ipeople iwho ihave itested ipositive ifor iCOVID-19 iin iKendari iin i2020. iAn ianalytical icross-sectional istudy iwas iused ito idesign ithis iresearch iand ithe isampling iwas idone iusing ipropotionsl irandom isampling itechnique. iData iwas icollected iusing isosial imedia, isuch ias iwhatsapp. iWhich ican ibe iaccessed ivia ia ismarthphone. iThe ipopulation iin ithis istudy i iwas iadults i(>17 iyears iold) iliving iin iKendari icity, iwhere ibased ion istatistical i idata iin i2019, ithe itotal ipopulation i211,247 ipeople. iThe isample iparticipants iwere ithe ipeople iof iKendari icity, iamounting ito i384 ipeople. iData icolletion iwas idone ionline iusing igoogle iform. iThe idata iwere ithan ianalized iwith iboth iunivariate iand ibivariate ianalysis iusing ithe ichi isquare itest. iThe iresults iof ithis istudy iindicated ithat ithere iwas ia irelationship ibetween istigma iand ipublic iknowledge i(p ivalue i= i0,001< i0,05), ibetween istigma iand ipeople’s iperceptions i(p ivalue i= i0,000< i0,05), iand ibetween istigma iand ithe irole iof ihealth iworkers i(p ivalue i= i0,000<0,05) itowards ipeople iwho ihave itested ipositive ifor iCOVID-19. iIt ican ibe iconcluded ithat ithere iis ia isignificant irelationship ibetween istigma iknowledge, iperceptions iand ithe irole iof ihealth iworkers itowards ipeople iwho ihave itested ipositive ifor iCOVID-19 iin iKendari iin i2020